Electroplating of Aerosol Jet‐Printed Silver Inks. Issue 10 (6th June 2021) - Ohiri, Korine A.; Nowicki, Nicholas M.; Montalbano, Timothy J.; Presley, Michael; Lazarus, Nathan S.
Abstract : Aerosol jet printing of silver inks is a promising approach for 3D printing of electronics, particularly for obtaining very complex circuits with high‐resolution conductive pads and traces. Common silver inks are however not competitive with traditional bulk metal conductors, requiring sintering at high temperatures as well as having significant porosity that can result in early failure. Herein, the possibility of using electroplating to deposit bulk metal copper on aerosol jetted inks is investigated, and more than an order of magnitude reduction in electrical resistivity is shown. The plating rate, resistivity, and adhesion are characterized, along with the morphology of the resulting deposits. This approach is then shown to allow high‐strength soldering to the electroplated metal traces, demonstrating the capability of this technology for integration of soldered surface mount components with aerosol jet‐printed electronics. Abstract : Herein, electroplating to deposit bulk metal copper on aerosol jet printed inks is investigated, showing more than an order of magnitude reduction in electrical resistivity. The plating rate, resistivity, and adhesion are characterized, along with the morphology of the resulting deposits.